Implementasi Kewenangan Pemerintah Daerah dalam Pengawasan Kepatuhan Pembayaran Pajak Hiburan Konser Musik di Kabupaten Sleman - Fidecia Masayu Sharrla; Siti Rahma Novikasari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
This study aims to analyze the implementation of the Sleman Regency Government's authority in supervising compliance with entertainment tax payments in music concerts. Entertainment tax is an important component of Regional Original Income (PAD), with a self-assessment method regulated in Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments (HKPD Law). Sleman Regency has a strong entertainment sector dynamic with many national and international concerts, however, pre-research results indicate potential non-compliance such as ticket reporting manipulation, tax evasion through disguised activities, and non-transparency of the number of tickets sold. This study uses an empirical juridical method to assess the implementation of supervision, through interviews with the Sleman Regency BPKAD Office and three Concert Promoters, as well as document analysis related to reporting procedures, ticket distribution, and field supervision mechanisms. The results show that the Sleman Regency Government has implemented preventive supervision through direct monitoring, but repressive supervision regarding the application of administrative sanctions in the form of a 1% sanction of tax debts according to Regional Regulation Number 7 of 2023 has not been carried out. Although promoter compliance is considered relatively high, challenges remain, including limited supervisory human resources, coordination between police agencies and tourism agencies, and weak transparency in ticket reporting. This study recommends strengthening digital reporting, integrating the licensing system with tax verification, and routine audits to prevent local revenue leakage. These findings are expected to contribute to improving regional tax governance based on accountability and legal certainty.